Mekanisme Penyaluran Program Bantuan Kartu Keluarga Sejahtera Berbasis Cashless di Kelurahan Lewoleba - nur holifah (FISIP UWP, 2020)
Indonesia is known as a developing country, one of the characteristics of developing countries is seen from the mechanism of economic development. Economic development in Indonesia is currently faced with cases of increasing poverty rates. The government issues various policies/programs to reduce poverty in Indonesia. One of them is the Presidential Instruction of the Republic of Indonesia Year 2014 concerning the Implementation of the Savings for Prosperous Families Program, the Smart Indonesia Program, and the Healthy Indonesia Program to Build Productive Families. This study aims to find out how the mechanism for distributing cashless-based KKS assistance programs in Lewoleba Village, Lembata Regency, East Nusa Tenggara. The theory used is the theory of public policy. This type of research is descriptive qualitative. Data collection techniques are interviews, observation, and documentation. Sampling Purposive sampling technique. Data analysis used is collection, reduction, display, and verification. The results of this study are the mechanism for distributing cashless-based KKS program assistance to the community in Lewoleba Village, Lembata Regency, East Nusa Tenggara has been running according to the procedures established by the Control Team for the Implementation of Non-Cash Social Assistance Distribution and is well conditioned by the Village Government and all elements involved from the stage of socialization to the process of distributing aid involved in a transparent manner. This KKS program really helps the poor in Lewoleba Village in meeting their daily needs, in order to improve the quality of primary nutrition for the local community.